Rancang Bangun Aplikasi Self Planning & Motivation Untuk Membantu Keberhasilan Studi Mahasiswa - Arijuddin, Muhammad; Sutomo, Erwin; Suhandiah, Sri (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
National Standart of College ( NSC ) is a policy created by Indonesia Government to arrange period of study of college student. NCS is arranged in Ministerial Regulation of Education and Cultural no. 49 of 2014. On article no. 17 clause 3 mentioned that Bachelor has 4 to 5 years maximum period of study and Diploma III has 3 to 4 years maximum period of study. According to Stikom Surabaya data center, the students of Infomation Systems department who able to graduate in predetermined time is in low number and have decreased every year. Wherefore, the students doesn’t have planning and motivation to complete their study in time. Based on the issues, therefore a feature of self planning and motivation application is developed to help increase student’s ability to complete the study in time. The application is engaged by SDLC ( System Development Life Cycle ) method. The function of SDLC is to describe the stages of self planning and motivation application in making. The result of the trial is the application able to help to plan the final score accord to the target of each subject per semester. Also the application able to give motivation and as a motivation reminder fot the student in every semester.